2013
DOI: 10.1051/0004-6361/201321520
|View full text |Cite
|
Sign up to set email alerts
|

Kinematics and chemical properties of the Galactic stellar populations

Abstract: Aims. We analyzed chemical and kinematical properties of about 850 FGK solar neighborhood long-lived dwarfs observed with the HARPS high-resolution spectrograph. The stars in the sample have log g ≥ 4 dex, 5000 ≤ T eff ≤ 6500 K, and −1.39 ≤ [Fe/H] ≤ 0.55 dex. The aim of this study is to characterize and explore the kinematics and chemical properties of stellar populations of the Galaxy in order to understand their origins and evolution. Methods. We applied a purely chemical analysis approach based on the [α/Fe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

47
202
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 158 publications
(253 citation statements)
references
References 64 publications
(161 reference statements)
47
202
1
Order By: Relevance
“…This result is in agreement with previous studies, (e.g. Adibekyan et al 2013;Bensby et al 2014;Nidever et al 2014, most recently); see also Bensby et al (2007), Kordopatis et al (2013bKordopatis et al ( , 2015 for further evidence of metal-rich, thick-disc stars, defined kinematically. We find that the dispersion in [Mg/Fe] at fixed iron abundance for thick-disc stars is marginally smaller than the values derived for thin-disc stars.…”
Section: The High-metallicity Extent Of the Thick Discsupporting
confidence: 93%
See 2 more Smart Citations
“…This result is in agreement with previous studies, (e.g. Adibekyan et al 2013;Bensby et al 2014;Nidever et al 2014, most recently); see also Bensby et al (2007), Kordopatis et al (2013bKordopatis et al ( , 2015 for further evidence of metal-rich, thick-disc stars, defined kinematically. We find that the dispersion in [Mg/Fe] at fixed iron abundance for thick-disc stars is marginally smaller than the values derived for thin-disc stars.…”
Section: The High-metallicity Extent Of the Thick Discsupporting
confidence: 93%
“…This overlap in metallicity was already suggested from the α-abundance trends derived from very high-resolution studies of stars in the immediate solar neighbourhood (d < 100 pc; e.g. Reddy et al 2006;Adibekyan et al 2013;Bensby et al 2014;Nissen 2015), and by Nidever et al (2014) for stars in a wide range of Galactic radii (0 R 15 kpc). We can further assess the presence of thin-disc stars below [Fe/H] = −0.5 dex by making a rough separation of the stars within a given [Fe/H] bin into either high-α ([Mg/Fe] > 0.3 dex) or low-α ([Mg/Fe] < 0.2 dex, see also Sect.…”
Section: Azimuthal Velocity Componentsupporting
confidence: 54%
See 1 more Smart Citation
“…A similar behaviour is observable for Galactic field stars where the older thin and thick disc field dwarfs from Bensby et al (2014) yield more positive [α/Fe] ratios than the younger field dwarfs with thin disc kinematics. The similarity in [α/Fe] between the thin and thick disc clusters with ages of 4 to 9 Gyr suggest that age cannot be the key variable, but different proportions of Type II to Type Ia supernovae products in clusters formed at dif- Adibekyan et al 2013;Bensby et al 2014). Although the origin of such objects is still in debate, Adibekyan et al (2011Adibekyan et al ( , 2013 have suggested a possible origin of these α-enhanced metal-rich stars in the inner Galaxy (bulge) followed by a subsequent migration to the solar vicinity.…”
Section: [α/Fe] Vs Cluster's Agementioning
confidence: 99%
“…This model needs to be improved to account also for the gap in the [α/Fe]-[Fe/H] relation seen for a long time in high-resolution spectroscopic data in the solar vicinity (e.g., Adibekyan et al 2013;Bensby et al 2013;Fuhrmann 2004) and more recently found in a range of Galactic radii using APOGEE data (Anders et al 2014;Nidever et al 2014). This separation into low-and high-[α/Fe] sequences (sometime referred to as the thin and thick discs) 8 is most likely the result of a gap in the SFH at high redshift, as first suggested in the Two-Infall Model by Chiappini et al (1997).…”
Section: Comparison With Observationsmentioning
confidence: 99%